NF-κB activation and potentiation of proinflammatory responses by the Helicobacter pylori CagA protein - Brandt, Sabine; Kwok, Teriy; Hartig, Roland; König, Wolfgang; Backert, Steffen (Proceedings of the National Academy of Sciences of the United States of America, 2005)
The Helicobarter pylori immunodominant protein, CagA, is associated with severe gastritis and carcinoma. Injection of CagA into gastric epithelial cells by type IV secretion leads to actin-cytoskeletal rearrangements and cell scattering. CagA has been reported to have no role in the induction of transcription factor NF-κB and IL-8, which are crucial determinants for chronic inflammation. Here, we provide several lines of evidence showing that CagA is able to induce IL-8 in a time- and strain-dependent manner. We also show that by exchanging specific cagA genes, high IL-8-inducing H. pylori strains could be converted into low inducing strains and vice versa. Our results suggest that IL-8 release induced by CagA occurs via a Ras→Raf→Mek→ Erk→NF-κB signaling pathway in a Shp-2- and c-Met-independent manner. Thus, CagA is a multifunctional protein capable of effecting both actin remodeling and potentiation of chemokine release. © 2005 by The National Academy of Sciences of the USA.
Created from Fastlane, Scopus look-up
Keywords: Molecular pathogenesis; Pathogenicity island; Type IV secretion; Virulence